Computational Insights in DNA Methylation: Catalytic and Mechanistic Elucidations for Forming 3-Methyl Cytosine. (7th February 2022) - Almatarneh, Mansour H.; Kayed, Ghada G.; Altarawneh, Mohammednoor; Zhao, Yuming; Verma, Amita
Abstract : Methylation at C5 position of cytosine (5 mC) is the most abundantly occurring methylation process at CpG island, which has been well known as an epigenetic modification linked to many human diseases. Recently, another methylation approach has been discovered to show that DNA methyltransferases (DNMTs) promote the addition of the methyl group at position 3 to yield 3 mC. The existence of 3 mC can cause severe damages to the DNA strand, such as blocking its replication, repair, and transcription, affecting its stability, and initiating a double-strand DNA break. To gain a deeper insight into the formation of 3 mC, we have performed density functional theory (DFT) modeling studies at different levels of theory to clearly map out the mechanistic details for this new methylation approach. Our computed results are in harmony with pertinent experimental observations and shed light on a crucial off-target activity of DNMTs.